Análisis de requerimientos para el desarrollo de un sistema informático de control de internos en el Centro de Rehabilitación Social de la ciudad de Babahoyo - Garaicoa Loor, Daniel Fernando (2020)
The human being has been carrying out the information processes in a manual way so it took a long time to process documents, there are many social rehabilitation centers that do not have a data control system that causes discomfort in the relatives of inmates to to be able to carry out the information process in a more truthful and effective way, due to this problem, a case study was carried out where it was realized that the information is annotated in notebooks and later stored in filing cabinets, therefore it is very difficult to obtain information In order to carry out a procedure more quickly, in this case study the qualitative and quantitative methodology and the survey, interview and direct observation technique have been used